2016
DOI: 10.1016/j.rpped.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Duração do aleitamento materno em prematuros acompanhados em serviço de referência secundário

Abstract: The median duration of breastfeeding in preterm infants was below the recommended one and discontinuation was associated with gestational <32 weeks and the fact that the infant was no longer receiving exclusive breastfeeding in the first outpatient visit. When these two variables were associated, their negative effect on the median duration of breastfeeding was potentiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
(17 reference statements)
0
18
0
8
Order By: Relevance
“…Probably, because of this approach, our study evidenced a high proportion of breastfeeding in the first month of adjusted age, even if not exclusive. Freitas et al (2016) reported the duration of breastfeeding in preterm infants followed during the first year of life, dividing them into two groups: lower and greater than 32 weeks gestation 15 , and later analyzing the duration of breastfeeding between the children who were in exclusive breastfeeding at the first appointment or not. They found a median of breastfeeding in the total population (lower and greater than 32 weeks) of 5 months, but in the group of lower gestation age the median was 4.2 months when in exclusive breastfeeding at the first appointment, and of 1.2 months when breastfeeding was complemented with formula at the first appointment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably, because of this approach, our study evidenced a high proportion of breastfeeding in the first month of adjusted age, even if not exclusive. Freitas et al (2016) reported the duration of breastfeeding in preterm infants followed during the first year of life, dividing them into two groups: lower and greater than 32 weeks gestation 15 , and later analyzing the duration of breastfeeding between the children who were in exclusive breastfeeding at the first appointment or not. They found a median of breastfeeding in the total population (lower and greater than 32 weeks) of 5 months, but in the group of lower gestation age the median was 4.2 months when in exclusive breastfeeding at the first appointment, and of 1.2 months when breastfeeding was complemented with formula at the first appointment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this knowledge, breastfeeding rates among preterm newborn are still low 11 . Few studies report the duration of breastfeeding after hospital discharge, throughout the first year of life, among newborn below 33 weeks of gestation [12][13][14][15] . This knowledge is important for the promotion of breastfeeding maintenance strategies in this group of infants.…”
Section: Introductionmentioning
confidence: 99%
“…However, these PN present late onset and shorter duration of breastfeeding (BF) when compared to full-term babies (4)(5) . Although researches have showed improve in BF among premature babies, EBF rates in this group are lower than those recommended by the WHO, which considers a "good" or "very good" situation when 50 to 89% and 90% to 100%, respectively, of children under six months of age are in EBF, regardless of gestational age (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding has benefits for mother and infant, and is recommended exclusively and freely during the first six months of life (Victora et al., ). However, when the neonate requires hospitalization in a neonatal intensive care unit (NICU), the establishment of breastfeeding can be a challenge for the mother–infant dyad (Freitas, Lima, Carlos, Priore, & Franceschini, ; Parker, Sullivan, Krueger, & Mueller, ).…”
Section: Introductionmentioning
confidence: 99%